Manfaat Pendampingan Pemberdayaan Masyarakat dalam Program Pengembangan Berorganisasi di Jabodetabek - Bambang Sutarto; Supatmin Supatmin; Budhi Prabowo (Indonesian Journal of Society Engagement, 2023)
The Association of Overseas Argapuri is one of the social communities in Jabodetabek society. The movement of this association can be further enhanced by providing assistance in the form of training and additional capacity building. One of the assistance that can be done is to provide training regarding the use of information technology. Having sufficient knowledge and insight into skills will later become the provision to be able to metamorphose into an independent person who can not only be useful for himself, but also be able to provide benefits to society and the universe after living in the Argapuri Migrant Association. Community service activities focus on graphic design training for members of the Agapuri overseas community. This training is expected to provide added value for the development of the Argapuri migrant community. So that the agenda for using information technology can run sustainably in the Argapuri migrant community and have a significant impact.